Efisiensi Kerapatan Tananaman Pakcoy (Brassica Rapa) terhadap Kualitas Air untuk Mendukung Kelangsungan Hidup Ikan Nila - Asnan Ridoanrisna; Robin Robin; Novita MZ (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Asnan Ridoanrisna. Efficiency Of Pakcoy Plants (Brassica Rapa) In Maintaining Water Quality To Support The Survival Rate Of Tilapia. Under Guidance By Robin And Novita Mz. Tilapia is a freshwater fish commodity with high economic value. According to data from the Central Bureau of Statistics (BPS), tilapia exports reached 12.29 thousand tons with a value of USD 78.44 million. Tilapia farming faces the risk of mortality which can lead to economic losses, one of which is caused by organic pollution. To address this issue, this research employs phytoremediation methods with varying plant densities to improve water quality and tilapia survival. The study was conducted with four treatments: A75 (plant density 75% of the aquarium surface area), A50 (50%), A25 (25%), and A0 (no plants), using an aquarium size of 60 x 30 x 50 cm³. Each treatment received chicken manure at 1.8 grams per aquarium and 40 tilapia fish per aquarium. Observations were made over 15 days in March 2023, measuring physical and chemical water parameters including DO, pH, TDS, temperature, and ammonia, as well as calculating the survival rate of tilapia. Using a Completely Randomized Design (CRD), the study found that treatment A75 achieved the highest survival rate at 62.5%. This result indicates that higher plant density in the phytoremediation method is more effective in maintaining water quality and supporting tilapia survival.